2016
DOI: 10.1089/dna.2015.2993
|View full text |Cite
|
Sign up to set email alerts
|

Glycolic Acid Silences Inflammasome Complex Genes,NLRC4andASC, by Inducing DNA Methylation in HaCaT Cells

Abstract: AHAs (α-hydroxy acids), including glycolic acid (GA), have been widely used in cosmetic products and superficial chemical peels. Inflammasome complex has been shown to play critical roles in inflammatory pathways in human keratinocytes. However, the anti-inflammatory mechanism of GA is still unknown. The aim of this study is to investigate the relationship between the expression of the inflammasome complex and epigenetic modification to elucidate the molecular mechanism of the anti-inflammatory effect of GA in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 52 publications
0
5
0
Order By: Relevance
“…Maternal fluoxetine exposure has been shown to result in posttranslational histone modifications and altered DNA methylation in the offspring (Boulle et al, 2016;Toffoli et al, 2014). There is also some evidence in the literature that demonstrates epigenetic regulation of Elovl6 and core components of NLRP3 inflammasome (Corominas et al, 2015;Meier, Drexler, Eberle, Lefort, & Yazdi, 2016;Tang et al, 2016). Moreover, knockdown of sirtuin 1 (SIRT1), a NAD + -dependent deacetylase has been demonstrated to enhance activation of the NLRP3 inflammasome in HUVEC cells (Li et al, 2017) and inhibition of SIRT1 in hepatocytes results in an upregulation of de novo lipogenesis related genes (Nassir & Ibdah, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…Maternal fluoxetine exposure has been shown to result in posttranslational histone modifications and altered DNA methylation in the offspring (Boulle et al, 2016;Toffoli et al, 2014). There is also some evidence in the literature that demonstrates epigenetic regulation of Elovl6 and core components of NLRP3 inflammasome (Corominas et al, 2015;Meier, Drexler, Eberle, Lefort, & Yazdi, 2016;Tang et al, 2016). Moreover, knockdown of sirtuin 1 (SIRT1), a NAD + -dependent deacetylase has been demonstrated to enhance activation of the NLRP3 inflammasome in HUVEC cells (Li et al, 2017) and inhibition of SIRT1 in hepatocytes results in an upregulation of de novo lipogenesis related genes (Nassir & Ibdah, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…We demonstrated that GA at a low concentration (0.1 mM) either alone or with UVB radiation reduced the expression of inflammasome genes in NHEKs and HaCaT cells. These genes include NLRC4 and ASC, and are downregulated through epigenetic modification by increasing total DNA methyltransferase activity [ 10 ]. Through this mechanism, GA can reduce NLRC4 and ASC gene expression, thereby resulting in inflammasome collapse and decreasing the quantity of inflammasome downstream cytokine interleukin (IL)-1β released.…”
Section: Ahas Peeling and Uv Irradiationmentioning
confidence: 99%
“…Our laboratory has analyzed a series of related studies on AHAs, which we also highlight in this article [ 8 , 9 , 10 , 11 , 12 , 13 , 14 , 15 , 16 , 17 ]. GA regulates several signaling pathways, such as epigenetic factors and apoptotic mediators.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, other studies have shown that HDAC6 and HDAC2 are also involved in the activation of NLRP3 inflammasomes in inflammatory diseases such as tuberculosis infection [ 119 , 120 ]. Glycolic acid stimulation of human immortalized keratinocytes induces DNMT3B recruitment in NLRC4 inflammasome and inhibits the transcriptional expression of NLRC4 and ASC, which may lead to the blockage of NLRC4 inflammasome assembly [ 121 ].…”
Section: Role Of Chromatin Modifiers In Human Diseasesmentioning
confidence: 99%